Answer:
The general form of the equation is x² + y² + 6x - 24y + 128 =0 .
Explanation:
The general form of the equation is written in the general form
(x - h)² + (y - k)² = r²
As given the figure in the question
Centre of the circle is A (-3 , 12) and radius is 5 .
Thus
(x - (-3))² + (y - 12)² = 5²
5² = 25
(x - (-3))² + (y - 12)² = 5²
(x + 3)² + (y - 12)² = 25
(By using the formula (a + b)² = a² + b² + 2ab , (a - b)² = a² + b² - 2ab)
Thus
x² + 3² + 2 × 3 × x + y² + 12² - 2 × 12 × y = 25
3² = 9
12² = 144
x² + 9 + 6x + y² + 144 - 24y = 25
x² + y² + 6x -24y + 9 + 144 - 25 = 0
x² + y² + 6x - 24y + 128 =0
Therefore the general form of the equation is x² + y² + 6x - 24y + 128 =0 .